The inverse source problems for the Helmholtz operators - Luc, Le Trong (Journal of Computer Science and Cybernetics, 2016)
The paper is devoted to studying the inverse source  problem for  the Helmholtz equations  as  investigating solution sets (or information  content) because of  its ill-posedness, consisting of source distributions located on a  closed domain considered, which create the potentials known  outside  that closed domain and unknown on it.